Variety-Seeking Behavior in Consumption: A Literature Review and Future Research Directions - Zhang, Yuan (Frontiers in Psychology, 2022)
Variety-seeking is a popular choice strategy in consumers’ daily lives, and many factors influence it. This study conducted a narrative and structured literature review based on three popular online academic databases to understand how researchers used influencing factors, adopted theoretical perspectives and underlying mechanisms, and developed measure methods in their studies. This paper consolidated and analyzed 61 articles on variety-seeking behaviors in consumer research, including empirical studies spanning from 2000 to 2021. This paper primarily focused on articles published at top tiers in marketing literature. From these articles, a collection of internal and external factors, theoretical perspectives, underlying mechanisms, and measure methods adopted was summarized and tabulated for easy reference and comprehension. A research framework was developed to illustrate the relationships between influence factors and variety-seeking proposed by previous researchers. The literature review may not be exhaustive because variety-seeking behaviors could involve various research topics; however, the proposed research framework and suggested directions may be representative references for future research. This study is a more comprehensive literature review of variety-seeking behaviors in consumption research after 2000, and it contributes to a better understanding of the causes and effects of variety-seeking behaviors in consumption.